Hate speech in digital space: A sociolinguistic analysis of the “CIN” domestic violence case on Instagram - Putri Ambarwati; Sailal Arimi (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study aims to analyze the forms and gender-based differences of hate speech produced by male and female netizens in responding to the domestic violence case involving Cut Intan Nabila on Instagram. Employing a sociolinguistic approach, this research applies Speech Act Theory (Austin, 1962; Searle, 1979) and the concept of hate speech in digital communication. Data were collected from netizens’ comments on related posts and analyzed to identify linguistic forms and gender variations in hate expressions. Unlike previous studies that primarily focused on political or ethnic hate speech, this research situates the phenomenon within Indonesia’s digital culture, reflecting shifts in social values, public morality, and gender relations in online spaces. The findings reveal significant differences in the linguistic forms and strategies used by male and female netizens, illustrating how each gender expresses emotion and moral stance through hate speech. This study contributes to digital sociolinguistic research by highlighting the role of language in shaping social interaction and gender awareness within Indonesia’s digital discourse.   Penelitian ini bertujuan untuk menganalisis bentuk serta perbedaan ujaran kebencian antara netizen laki-laki dan perempuan dalam merespons kasus kekerasan dalam rumah tangga (KDRT) yang melibatkan Cut Intan Nabila di Instagram. Kajian ini menggunakan pendekatan sosiolinguistik dengan memanfaatkan teori tindak tutur (Austin, 1962; Searle, 1979) dan konsep ujaran kebencian dalam komunikasi digital. Data dikumpulkan dari komentar netizen pada unggahan terkait kasus tersebut dan dianalisis untuk mengidentifikasi bentuk ujaran kebencian serta variasinya berdasarkan gender penutur. Berbeda dari penelitian terdahulu yang cenderung menyoroti ujaran kebencian dalam konteks politik atau etnis, penelitian ini menempatkan fenomena ujaran kebencian dalam konteks budaya digital Indonesia yang merefleksikan pergeseran nilai sosial, moralitas publik, dan relasi gender di ruang daring. Hasil penelitian menunjukkan adanya perbedaan dalam bentuk dan strategi kebahasaan antara ujaran kebencian laki-laki dan perempuan, di mana perbedaan tersebut mencerminkan cara masing-masing gender mengekspresikan emosi dan posisi moralnya. Penelitian ini berkontribusi dalam memperkaya kajian sosiolinguistik digital serta menegaskan peran bahasa dalam membentuk dinamika sosial dan kesadaran gender di era media digital.